1982
DOI: 10.1111/j.1365-2265.1982.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids, Postheparin Plasma Lipase Activities and Glucose Tolerance in Patients With Prolactinoma

Abstract: prolactinoma is associated with metabolic abnormalities characterized by hyperlipidaemia, low plasma LPL activity and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
4

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
3
26
4
Order By: Relevance
“…In agreement with the results of other reported studies [1][2][3], fasting plasma glucose concentrations were not increased in hyperprolactinemic women. Premeal and postprandial glucose values were not significantly higher in these patients than in normal women.…”
Section: Commentsupporting
confidence: 83%
See 3 more Smart Citations
“…In agreement with the results of other reported studies [1][2][3], fasting plasma glucose concentrations were not increased in hyperprolactinemic women. Premeal and postprandial glucose values were not significantly higher in these patients than in normal women.…”
Section: Commentsupporting
confidence: 83%
“…Premeal and postprandial glucose values were not significantly higher in these patients than in normal women. The findings differ from previous reports describing a reduced glucose tolerance in hyperprolactinemic patients [1][2][3]. How ever, Katz et al [4] found a normal intravenous glucose tolerance in patients with prolactinoma.…”
Section: Commentcontrasting
confidence: 56%
See 2 more Smart Citations
“…In rats and humans, PRL increases β-cell proliferation, insulin gene transcription and glucose-dependent insulin secretion [73,74,75,76]. In men and women with chronic hyperprolactinemia, post-prandial hyperinsulinemia and exaggerated insulin secretory response to glucose have been demonstrated [77,78,79]. Interestingly, pancreatic β cells also express dopamine receptors and treatment with the selective D 2 R agonist quinpirole causes the inhibition of glucose-stimulated insulin secretion [80].…”
Section: Discussionmentioning
confidence: 99%